Formulation, characterization and evaluation of mRNA-loaded dissolvable polymeric microneedles (RNApatch) - Koh, Kai Jun; Liu, Yi; Lim, Seng Han; Loh, Xian Jun; Kang, Lifeng; Lim, Chee Yen; Phua, Kyle K. L. (Scientific reports, 2018)
In this paper, we report a proof of concept study on the fabrication, characterization and therapeutic evaluation of in vitro transcribed messenger RNA (mRNA) loaded in a dissolving microneedle patch (RNApatch). We show that low molecular weight polyvinylpyrrolidone (PVP) can directly be used without further purification for RNApatch fabrication with no detectable mRNA degradation. Physical and functional integrity of mRNA stored within the RNApatch are completely preserved for at least 2 weeks under ambient conditions. While the loading of mRNA into RNApatch is limited by the solubility of mRNA in concentrated PVP solution, mechanical strength of RNApatch is not compromised by the presence of mRNA. RNApatch can mediate in vivo transgene expression of mRNA encoding luciferase for up to 72 hours and transfection efficiency and kinetics mediated by RNApatch compares favorably to subcutaneous injection. Interestingly, mRNA transfection efficiency does not correlate with contact surface area but instead increases with deeper delivery depths. In an E.G7-OVA immunotherapy model, RNApatch induces slightly higher cellular and humoral immune responses compared to subcutaneous injection. In conclusion, RNApatch is a viable delivery platform for mRNA and represents an attractive option with significant translation potential for the delivery of mRNA therapeutics.